ANALISIS KONDISI KOMPONEN-KOMPONEN TEKNOLOGI PENGOLAHAN DI INDUSTRI TEH CURAH INDONESIA - Rohayati Suprihatini E.Gumbira Sa’id , Marimin dan Djumali Mangunwidjaja (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACTIn order to accelerate increasing of technology capability of made tea industries in Indonesia, it requires study on technology components. Surveys was conducted on eight made tea companies. Ordered weighted averaging (OWA) analysis was applied to determine level of technology components condition. Non numeric multi-criteria multi-person analysis was applied to determine the level of technology capability in Indonesian made tea industry. The research results show that the level of technology component condition namely technoware, humanware, infoware, and orgaware are still in medium level, respectively. The technology component condition should be in high level, in order to increase technology capability to medium level. In term of strategic management of improving the capability of technology, most of respondents (75%) selected improvement continuously. Therefore, this strategy should be treated as an action program of Indonesian Tea Association (ITA) as well as government.Keywords : capability, technology, processing, made tea.